EKSTRAKSI LEMAK DARI BIJI TENGKAWANG TUNGKUL (SHOREA STENOPTERA BURCK) DENGAN BEBERAPA PELARUT ORGANIK - Bambang Wiyono (Jurnal Penelitian Hasil Hutan, 1989)
The  purpose   of  this  research   is  to  study   the  effect  of  several  organic  solvents   and  storage  time  on fat  content, acidify,   and  free  fatty acid  content   of  Illipe  nut  hernels   (S.   stenoptera    Burck).  The  treatment   effect   was analysed  by using a randomized  complete   block  design.The  result  indicated   that  storage  time   reduced  moisture   content   of  Illipe  nut  kernels   (S. stenoptera   Burck),  but on the  contrary   the  storage  treatment    tended    to  increased  the  ash  content.   Extended  storage  time  decreased  fat  content significantly.   Acetone    solvent   extraction   produced   highly  significantly    effect   on  fat  and  free  fatty  acid  content    than that  of  the  other  solvents.   Biochemical  activity   of  lllipe   nut   hernels  (S.   stenoptera  Burck)  degraded  the quality,  and  the rate of  degradation   was influenced   by  humidity   and temperature.   Therefore,     to  maintain.    good  kernels  quality,   optimum storage  condition  is desired.